Housing, the Neighborhood Environment, and Physical Activity among Older African Americans - Hannon, Lonnie (2012)
This study examines the association of neighborhood environment, as measured by housing factors, with physical activity among older African Americans. Context is provided on the effects of structural inequality as an inhibitor of health enhancing neighborhood environments. The study population included African Americans participating in the UAB Study of Aging (n=433). Participants demonstrated the ability to walk during a baseline in-home assessment. The strength and independence of housing factors were assessed using neighborhood walking for exercise as the outcome variable. Sociodemographic data, co-morbid medical conditions, and rural/urban residence were included as independent control factors. Homeownership, occupancy, and length of residency maintained positive associations with neighborhood walking independent of control factors. Housing factors appear to be predictive of resident engagement in neighborhood walking. Housing factors, specifically high rates of homeownership, reflect functional and positive neighborhood environments conducive for physical activity. Future interventions seeking to promote health-enhancing behavior should focus on developing housing and built-environment assets within the neighborhood environment.